Exploring the use of enhanced cone-beam CT technique to diagnose vertical root fracture. (June 2022) - Hu, Ziyang; Pan, Xiao; Hu, Yanni; Xu, Shi; Gao, Antian; Cao, Dantong; Lin, Zitong
Abstract: Objectives: To explore the feasibility of using sodium iodide (NaI)+dimethyl sulfoxide (DMSO)+ethyl alcohol+ethyl acetate as a cone-beam CT (CBCT) contrast agent in the diagnosis of vertical root fracture (VRF). Methods: 21 endodontically treated VRF teeth of 21 patients were collected in this study. All these 21 teeth were confirmed subtle fracture lines under transillumination, the number and position of fracture lines were recorded. All these patients had CBCT routine scanning (RS1) before extraction. After extraction, the teeth was performed micro-CT scanning and 3 in vitro CBCT scanning: CBCT routine scanning in vitro (RS2), CBCT enhanced scanning using meglumine diatrizoate (MD) as contrast agent(ES1); and CBCT enhanced scanning using NaI+DMSO+ethyl alcohol+ethyl acetate as contrast agent(ES2). The number of fracture lines was evaluated on all the 5 scanning modes and the accuracy of diagnosis was calculated. Results: In all, there were 43 fracture lines on the 21 teeth. The accuracy of detection of fracture lines of CBCT RS1, RS2, ES1, ES2 and micro-CT was 0%, 20.9% (9/43), 11.6% (5/43), 93% (40/43) and 95.3% (41/43) respectively. Significant differences were found between ES2 vs. RS2, ES2 vs. ES1 ( p < 0.01); however, no significant difference was found between ES2 vs. micro-CT ( p > 0.05). Conclusion: CBCT enhanced scanning using NaI+DMSO+ethyl alcohol+ethyl acetate as contrast agent could be a prospective technique in the diagnosis of VRF.